Antimicrobials as cornerstones and quick fixes Zimbabwean in healthcare and society: Health practitioners´ critical reflections on two stories of antimicrobial use as part of antimicrobial resistance (AMR) education. - Martin Mickelsson; Tungamirirai Simbini (PLOS Global Public Health)
Antimicrobials are often presented as key for the sustainability of healthcare as these pharmaceuticals are viewed as critical resources for much of modern medicine. Communicable diseases are a major contributing factor to morbidity and mortality in developing countries. The emergence of antimicrobial resistance (AMR) thus poses a significant challenge to global public health towards controlling these diseases and the SDG 3 Good health and well-being promoting calls for shared responsibility in preserving antimicrobials. This paper aims to explore health practitioners' understandings of the role of antimicrobials in healthcare and society and how this could inform antimicrobial resistance (AMR) education. Using a qualitative participatory research methodology, two participatory research workshops formed the empirical basis for the study and included 25 health practitioners from two major Zimbabwean central hospitals in the latter half of 2023. The focus of the workshops was on participants´ engagement with and discussions of two conceptual stories of antimicrobials in healthcare and society, as cornerstones which are key to the sustainability of healthcare and viability of modern medicine, and quick fixes that are used to mitigate but not resolve deeper and structural challenges as part of the Zimbabwean healthcare and society. During the workshops research data was collected through audio recordings supported in the analysis by contemporary field notes as well as written documentation created by the workshop participants. Three interconnected themes were identified as part of the results outlining how participants operationalised the two stories as part of AMR education. These included (i) preventing common infections, (ii) addressing risk factors, and (iii) engaging with societal inequalities. A key result was how the participating health practitioners highlighted the need to reduce reliance on antimicrobials which in turn necessitates a shift in focus towards preventive health actions such as improved hygiene, better water and sanitation as well as improved infection control. Such preventive efforts were furthermore linked in the participants´ discussions to structural challenges, including poor housing, limited access to clean water and inaccessible health care that was quoted as crucial to reduce infection risk and thus mitigate the need for antimicrobials in the first place. Bringing the identified themes and in-depth participant discussions together in the discussion, the paper presents a mirror model of antimicrobials in healthcare, highlighting how they are essential resources and cornerstones for healthcare while simultaneously and perpetuating systemic challenges in healthcare and society. The integration of this co-created knowledge as part of AMR education would contribute to a shift from the prevalent focus on preventing resistance to also consider the prevention of infections and the need for antimicrobials, including understanding and addressing the root causes of infections. Such a holistic approach to AMR education could promote more sustainable health practices, linking AMR challenges with broader societal and systemic challenges as part of more effective health educational efforts.